Novel Insights and Current Evidence for Mechanisms of Atherosclerosis: Mitochondrial Dynamics as a Potential Therapeutic Target - Li, Dan; Yang, Shengjie; Xing, Yanwei; Pan, Limin; Zhao, Ran; Zhao, Yixi; Liu, Longtao; Wu, Min (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular disease (CVD) is the main cause of death worldwide. Atherosclerosis is the underlying pathological basis of CVD. Mitochondrial homeostasis is maintained through the dynamic processes of fusion and fission. Mitochondria are involved in many cellular processes, such as steroid biosynthesis, calcium homeostasis, immune cell activation, redox signaling, apoptosis, and inflammation, among others. Under stress conditions, mitochondrial dynamics, mitochondrial cristae remodeling, and mitochondrial ROS (mitoROS) production increase, mitochondrial membrane potential (MMP) decreases, calcium homeostasis is imbalanced, and mitochondrial permeability transition pore open (mPTP) and release of mitochondrial DNA (mtDNA) are activated. mtDNA recognized by TLR9 can lead to NF-κB pathway activation and pro-inflammatory factor expression. At the same time, TLR9 can also activate NLRP3 inflammasomes and release interleukin, an event that eventually leads to tissue damage and inflammatory responses. In addition, mitochondrial dysfunction may amplify the activation of NLRP3 through the production of mitochondrial ROS, which together aggravate accumulating mitochondrial damage. In addition, mtDNA defects or gene mutation can lead to mitochondrial oxidative stress. Finally, obesity, diabetes, hypertension and aging are risk factors for the progression of CVD, which are closely related to mitochondrial dynamics. Mitochondrial dynamics may represent a new target in the treatment of atherosclerosis. Antioxidants, mitochondrial inhibitors, and various new therapies to correct mitochondrial dysfunction represent a few directions for future research on therapeutic intervention and amelioration of atherosclerosis.